2018
DOI: 10.1186/s13058-018-0942-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of CD4-positive T cell subsets in early breast cancer: a study based on the FinHer trial patient population

Abstract: BackgroundThe clinical importance of tumor-infiltrating cluster of differentiation 4 (CD4) T cells is incompletely understood in early breast cancer. We investigated the clinical significance of CD4, forkhead box P3 (FOXP3), and B cell attracting chemokine leukocyte chemoattractant-ligand (C-X-C motif) 13 (CXCL13) in early breast cancer.MethodsThe study is based on the patient population of the randomized FinHer trial, where 1010 patients with early breast cancer were randomly allocated to adjuvant chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 45 publications
3
51
1
1
Order By: Relevance
“…Furthermore, in a retrospective analysis of the FinHER trial, the B-cell attracting chemokine leukocyte chemoattractant–ligand (C–X–C motif) 13 (CXCL13) was independently associated with prognosis in triple-negative breast cancer. Other studies have also confirmed that B-cell signatures had a prognostic impact, particularly in basal-like and HER2-positive breast cancer subtypes [ 11 ]. In a further analysis, we examined the prognostic impact of different immune signatures in node-negative breast cancer patients and demonstrated a prognostic effect of a B-cell and T-cell signature, especially in HER2-positive breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, in a retrospective analysis of the FinHER trial, the B-cell attracting chemokine leukocyte chemoattractant–ligand (C–X–C motif) 13 (CXCL13) was independently associated with prognosis in triple-negative breast cancer. Other studies have also confirmed that B-cell signatures had a prognostic impact, particularly in basal-like and HER2-positive breast cancer subtypes [ 11 ]. In a further analysis, we examined the prognostic impact of different immune signatures in node-negative breast cancer patients and demonstrated a prognostic effect of a B-cell and T-cell signature, especially in HER2-positive breast cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 81%
“…The B-cell metagene was correlated with improved outcomes in highly proliferating node-negative breast cancer patients regardless of ER or HER2 status [ 9 ]. In a further study evaluating CXCL13 mRNA expression in the FinHER trial, CXCL13 as a marker of the humoral immune system was associated with favorable prognosis, particularly in triple-negative breast cancer (TNBC) [ 11 ]. One possible explanation for the finding that immune-related gene signatures have prognostic and predictive effects, particularly in the case of strongly proliferating tumors, especially TNBC or basal-like breast cancer, is the occurrence of an increased mutation load and neoepitopes that can induce or enhance an antitumor immune response [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that CD4+ TILs display a large degree of plasticity and the ability to differentiate into multiple sublineages in response to environmental cues [30]. CD4+ Th1 cells, CD4+ CTLs, and follicular helper T cells exert potent anti-tumor activity, whereas regulatory T cells or, under certain circumstances, CD4+ Th2 cells and CD4+ Th17 cells show tumor-promoting activity [30,31]. Thus, in further studies, analyses of CD4+ TIL subsets would be crucial to find the overall effect of heavy CD4+ TIL infiltration around HRnegative DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Since CD4 + TILs are expressed in many T cell subsets including T helper 1 (Th1) cells, T helper 2 (Th2) cells and Tregs, each of these may have a different impact on prognosis. Th1 cells secrete several cytokines such as interferon gamma (IFNg), transforming growth factor beta (TGFβ), tumor necrosis factor alpha (TNF), and interleukin 2 (IL-2) [31]. These cytokines are involved in the function of CD8 + TILs and protect against tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%